Deliberative democracy and resource management education - Siddiqui, Asif (My University, 2013)
Topics: Deliberative Democracy: The Theory, Deliberative Democracy and Climate Change, Deliberative Democracy: Successes and Failures, Overcoming the Deliberative Democracy Deficit, Edmonton Citizens’ Panel.
Presented on June 12, 2013 at the First PRME (Principles of Resource Management Education) Canada Regional Meeting – E3: Earth, Education, Economics held at Grant MacEwan University in Edmonton, Alberta.
Keywords: deliberative democracy